Measuring the academic advancement of kindergarten students (Journal of the College of Basic Education, 2023)
The current research aims to identify the academic advancement of the female students of the Kindergarten Department and the significance of the differences in the academic advancement of the female students of the Kindergarten Department according to the variable of the educational stage. 2022 In order to achieve the objectives of the current research, the two researchers adopted the Academic Advancement Scale prepared by (Ali, 2021), which adopted the Martin and Marsh model because it is the most consistent with the data of the current research and consists of (56) items distributed over the dimensions of academic advancement and by ( 14) paragraphs for each dimension, noting that the dimensions of academic advancement are (academic integration, academic flexibility, academic challenges, goal orientations) and the psychometric properties (honesty - stability) of the scale were verified. To treat the data statistically, the researcher used the Statistical Bag for Social Sciences (SPSS) program The following results were reached:1- The students of the kindergarten department enjoy a high level of academic advancement.2- It was found that there are differences in the academic advancement scale between the students of the Kindergarten Department according to the school stage in favor of the students of the first stage. The two researchers came out with some recommendations and proposals.Keywords: academic advancement, kindergarten students